APPLICATION OF CLOTHES FORM STRUCTURAL ANALYSIS IN MODERN CLOTHING CAD - Залкінд, Вікторія Вікторівна; Косенко, Оксана Ігорівна (Eastern-European Journal of Enterprise Technologies, 2012)
In the present paper we motivate for the usage of clothes’ form structural analysis in modern CAD systems for clothing design. This method substantially improves the quality of interaction between designer and constructor in mass production of clothes.